2022
DOI: 10.12775/bgss-2022-0003
|View full text |Cite
|
Sign up to set email alerts
|

Is the impact of COVID-19 on housing construction activity inside and outside a large city evident? The example of Łódź (Poland)

Abstract: The coronavirus pandemic has influenced cities’ shape and future. Telecommuting, teleconferencing, telelearning and e-commerce are creating a new environment of human life. These new factors should be added to the existing problems of urbanisation that are urban sprawl and depopulation. The authors of the paper decided to examine the intensity and spatial distribution of residential construction activity and residential real-estate trade in one of the biggest Polish cities – Łódź – and neighbouring municipalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…A source from Statista [30] reports that developers received 23.5% more building permits in March 2020 than in the same month of the previous year. Another study by M. Załęczna and A. Antczak-Stępniak [31] examined the intensity and spatial distribution of residential construction activity and trade in one of the largest cities in Poland. The study found that the COVID-19 pandemic had a significant impact on the construction industry, with a decrease in the number of building permits issued and actual construction work started.…”
Section: Changes In Housing Market In Poland During the Covid-19 Pand...mentioning
confidence: 99%
“…A source from Statista [30] reports that developers received 23.5% more building permits in March 2020 than in the same month of the previous year. Another study by M. Załęczna and A. Antczak-Stępniak [31] examined the intensity and spatial distribution of residential construction activity and trade in one of the largest cities in Poland. The study found that the COVID-19 pandemic had a significant impact on the construction industry, with a decrease in the number of building permits issued and actual construction work started.…”
Section: Changes In Housing Market In Poland During the Covid-19 Pand...mentioning
confidence: 99%